Five year outcome after primary coronary intervention for acute ST elevation myocardial infarction: results from a single centre experience. Issue 12 (6th April 2005) - Parodi, G; Memisha, G; Valenti, R; Trapani, M; Migliorini, A; Santoro, G M; Antoniucci, D
Abstract : Objectives: To analyse the five year outcome of unselected patients with acute myocardial infarction (AMI) treated by primary percutaneous coronary intervention (PCI). Setting: High volume PCI tertiary centre. Design and results: The study was based on a sample of 1009 consecutive patients with ST elevation AMI treated by primary PCI. The mean (SD) clinical follow up was 51 (21) months and the follow up rate was 97.8%. The overall mortality was 20% and cardiac mortality was 16%. Non-fatal reinfarction rate was 5% and additional revascularisation procedure rate was 19%. Hospitalisation for heart failure was needed by 42 patients (4%). The variables related to mortality in multivariate Cox analysis were age (hazard ratio (HR) 1.054, 95% confidence interval (CI) 1.039 to 1.069, p < 0.0001), cardiogenic shock (HR 2.985, 95% CI 2.157 to 4.129, p < 0.0001), previous myocardial infarction (HR 1.696, 95% CI 1.199 to 2.398, p = 0.0003), and the presence of multivessel coronary artery disease (HR 1.820, 95% CI 1.317 to 2.514, p = 0.0003). Each additional high risk feature was associated with a relative risk for five year death of 2.328 (95% CI 2.048 to 2.646, p < 0.0001). Conclusions: The satisfactory results of routine mechanical revascularisation strategy in AMI were maintained during several years of follow up. Patients at risk of death during long term follow up may be identified by simple clinical and angiographic characteristics, such as old age, cardiogenic shock, previous myocardial infarction, and multivessel coronary artery disease. The risk of death progressively increases with the number of these high risk features.